The effect of endurance exercise on muscle force generating capacity of the lower limbs - Bentley, D. J.; Zhou, S.; Davie, A. J. (Journal of Science and Medicine in Sport, 1998)
The purpose of this study was to investigate the recovery of muscle force generating capacity (FGC) of the lower limbs following a session of cycle exercise (CE). Fourteen male cyclists (mean +/- SD age 25 +/- 4 yrs and VO2max 65.8 +/- 5 ml x kg(-1)min(-1)) performed tests assessing lower limb muscle FGC at rest (pre-test), as well as 6 and 24 hrs following CE performed on a mechanically-braked cycle ergometer. The CE consisted of 30 min at a workload corresponding to the lactate (Dmax) threshold (+/-15 W), and four 60 s rides at 120% VO2max with one min rest between each ride. At the completion of the CE a 6 or 24 hr recovery period was initiated, after which, each subject's muscle FGC was measured. The analysis of lower limb muscle FGC included, (1) 6 s all-out cycle test; (2) a maximal isokinetic leg extension at 60, 120 and 180 degrees x s(-1); and (3) a maximal concentric squat jump. Statistical analysis showed that compared to pre-test levels, a significant reduction in both isokinetic peak torque at 60 degrees x s(-1) and isoinertial maximum force occurred after 6 hrs of recovery. Although not significant, reductions also occurred at 6 hrs of recovery in isokinetic peak torque at 120 and 180 degrees x s(-1), as well as maximum rate of force development (RFD) during the squat jumps. No significant differences were observed between isokinetic peak torque, maximum force or RFD pre-test and following the 24 hr recovery period, indicating these tests had returned to normal by this time. No significant differences were found between peak power (PP) during the 6 s cycle test, pre-test and following either 6 or 24 hrs of recovery. These findings confirm earlier research that maximal voluntary strength is reduced for at least 6 hours following exhaustive dynamic exercise. The reduction in muscle FGC should be considered when resistance training is scheduled after endurance exercise.